The lark - Anouilh, Jean; Fry, Christopher (London : Methuen & Co., 1961)
Longacre Theatre, Kermit Bloomgarden presents Julie Harris in "The Lark," a play by Jean Anouilh, adapted by Lillian Hellman, also starring Boris Karloff with Joseph Wiseman, Christopher Plummer, Theodore Bikel, Bruce Gordon, Paul Roebling, Roger De Koven, directed by Joseph Anthony, lights and settings by Jo Mielziner, costumes by Alvin Colt, music composed by Leonard Bernstein, production stage manager Bill Ross.
Longacre Theatre, week beginning February 13, 1956.
"The Playbill for the Longacre Theatre"--Cover.
Title devised by Library staff.
Cast: Christopher Plummer, Boris Karloff, Julie Harris, Ward Costello, Lois Holmes, John Reese, Roger De Koven, Joseph Wiseman, Michael Higgins, Theodore Bikel, Ann Hillary, Joan Elan, Paul Roebling, Rita Vale, Bruce Gordon, Richard Nicholls, Ralph Roberts, Edward Knight, Joe Bernard, Ruth Maynard, Elizabeth Lawrence, Michael Price, Michael Conrad, William Lennard, Milton Katselas, Edgar Grower. Choral singers: Russell Oberlin, Pauline Seim, Betty Wilson, Jean Hakes, Charles Bressler, Arthur Burrows, Brayton Lewis, by arrangement with the New York Pro Musica Antiqua.
In: Richard L. Coe Theater Programs Collection (Library of Congress).
Keywords: Joan, -- of Arc, Saint, -- 1412-1431; Theater programs -- New York (State) -- New York; Theater programs